EFFECT OF DIETARY INCLUSION OF SHEANUT CAKE (VITELLARIA PARADOXA) ON PERFORMANCE OF QUAILS - M. MAHENDER and S. M. BHOKRE, S. A. KOCHEWAD* KRISHNA DAIDA K. SARJAN RAO ; T. RAGHUNANDAN (Indian Journal of Animal Production and Management, 2017)
A trial was conducted on 160 quails to evaluate the level of inclusion of Sheanut cakein the diets using four dietary treatments at (0%) T1, (3%) T2, (6%) T3 and (9%) T4 level ofSheanut cake at Poultry Experimentation Station, College of Veterinary Science RajendranagarHyderabad. Significantly (P